Role of water in cyclooxygenase catalysis and design of anti-inflammatory agents targeting two sites of the enzyme - Manpreet Kaur (Nature Portfolio, 2020)
Abstract While designing the anti-inflammatory agents targeting cyclooxygenase-2 (COX-2), we first identified a water loop around the heme playing critical role in the enzyme catalysis. The results of molecular dynamic studies supported by the strong hydrogen-bonding equilibria of the participating atoms, radical stabilization energies, the pKa of the H-donor/acceptor sites and the cyclooxygenase activity of pertinent muCOX-2 ravelled the working of the water–peptide channel for coordinating the flow of H·/electron between the heme and Y385. Based on the working of H·/electron transfer channel between the 12.5 Å distant radical generation and the radical disposal sites, a series of molecules was designed and synthesized. Among this category of compounds, an appreciably potent anti-inflammatory agent exhibiting IC50 0.06 μM against COX-2 and reversing the formalin induced analgesia and carageenan induced inflammation in mice by 90% was identified. Further it was revealed that, justifying its bidentate design, the compound targets water loop (heme bound site) and the arachidonic acid binding pockets of COX-2.